Implementasi Hukum Waris Adat Batak Toba bagi Anak Perempuan di Desa Belang Malum Kecamatan Sidikalang Kabupaten Dairi - Ester Senov Fitriani Simanjuntak; Sri Hadiningrum (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the implementation of inheritance distribution for daughters under the Batak Toba customary inheritance law. The research employs a qualitative method with an empirical juridical approach. The empirical juridical approach is used to analyze the interaction between customary law and its application within the Batak Toba indigenous community. The data used in this study consist of primary and secondary data. Data collection techniques include interviews, observations, and documentation. The data analysis technique applied is qualitative analysis, which involves data reduction, data presentation, and verification or conclusion drawing. The findings reveal that the implementation of Batak Toba customary inheritance law in Belang Malum Village remains based on the patrilineal principle. Although the community still upholds the patrilineal system that positions sons as the main heirs, this practice has gradually shifted in line with societal changes, particularly regarding the recognition of daughters as heirs and their entitlement to inheritance. In practice, daughters now receive a share of the inheritance, with the form and proportion determined by family consensus, the economic condition of each child, and local traditions. This study recommends openness to social developments and national legal principles that promote justice and gender equality, as well as the enhancement of legal awareness and education through both formal and non-formal means.